Confronting Anxiety in the Era of COVID-19: Investigating the Prevalence and Impact on Daily Life in Bangladesh - Islam, Md Rashadul; Sony, Sabrina Amita; Imran, Md Ashik; Disha, Sadia Sinty; Murshed, Mortuja Kamal; Talukdar, Sutapa; Pramanik, Shishir Kanti; Masud, Mostafa Kamal; Kalam Azad, Muhammad Abdul; Al Shoeb, Mohammad Abdullah (Bioresearch Communications, 2023)
Background: The COVID-19 pandemic has brought about unprecedented stress levels and has significantly impacted daily life activities, including changes in food patterns, sleep disturbances, and reduced physical activity. This survey study aims to analyze the pervasiveness of generalized anxiety disorder (GAD) among Bangladeshi adults and its association with daily life activities. Methods: A randomized phone number generator was utilized to approach 1438 individuals aged 18 and above, out of which 412 participants volunteered for the study. Participants' anxiety level was estimated by using the GAD-7 score. Results: Out of the 412 respondents, 11.89% experienced severe anxiety, while 17.72% and 39.32% suffered moderate and mild anxiety, respectively. Severe anxiety was more prevalent among women (16%) than men (9.54%). The study found that sleeping for less than eight hours was associated with an increased likelihood of severe anxiety (OR = 4.87), while fewer changes in food habits (OR = 0.27), less online exposure (OR = 0.01), and engaging in some physical activity (OR = 0.20) were associated with the reduced likelihood of anxiety. Conclusion: This survey study highlights to give more emphasis of monitoring anxiety during a public health emergency like the COVID-19 pandemic. The findings of this study establish a significant correlation between GAD and everyday life activities, emphasizing the need to prioritize mental health initiatives during such unprecedented times. Bioresearch Commu. 10(1): 1378-1385, 2024 (January)